Effect of Nanoparticles for Silver and Chitosan on Growth Parameter of juvenile jinga Shrimp Metapenaeus affinis (H. Milne Edwards, 1837) under Laboratory Conditions - Abbas, Ashwaq; Ghazi, Abdulhussein H.; Sultan, Anteesar N. (Mesopotamian Journal of Marine Sciences, 2025)
In the study, the effect of silver and chitosan nanoparticles on growth parameters of Metapenaeus affinis were investigated, the highest weight was 1.88 + 0.65 g in Ag NPs and 1.82 + 0.67 g in Cs NPs, while in the control was 1.81 + 0.74 g. The highest length in the Ag NPs was 6.22 + 1.51 cm, chitosan reached 8.32 + 1.61 cm, while was 6.11 + 1.35 cm for the control treatment. The weight gain rate in the end experimental, the silver NPs treatment was 0.58 + 0.41 g, while in the Cs NPs reached 1.13 + 0.86 g, and in the control reached to 1.81 + 0.74 g. The highest relative growth rate (%) was achieved in the Cs NPs treatment 49.2 % compared to 44.6% in silver NPs and 2.39 % in the control. While the highest specific growth rate (%) was achieved in the Cs NPs, it was 1.24 and the lowest rate was 1.08 in the control treatment. The highest rate of daily growth rates (g/day) was recorded in the Cs NPs treatment, reaching 0.045 g/day. The highest survival and molting rate were achieved in the Cs NPs treatment, 76% and 28 % respectively, in the Ag NPs were 52 % and 26% respectively and in the control were 64 % and 18 % respectively. The data were analyzed by using the (SPSS v.20) to test for significant differences between means and the LSD test at a significance level of 0.05. The green tea Camellia sinensis extract showed good results in manufacturing silver nanoparticles (Ag NPs) and chitosan nanoparticles (Cs NPs). The results of the UV-visible spectrum examination showed that the absorbance of Ag NPs was 456 nm and Cs NPs were 271 nm. The atomic force microscope (AFM) examination revealed that the size of silver NPs was 88.4 nm and Cs NPs was 43.33 nm